Prevalence and Outcome of Hyponatremia in Critically Ill Children Admitted to The Pediatric Intensive Care Unit in Tertiary Care Hospital – A Cohort Study - Rishika Jothi Perumalsamy; Sheeja Sugunan; Rekha Krishnan (JK Science)
Background: Hyponatremia is the most common electrolyte disturbance observed in hospitalized children with an incidence of 15 - 45%. The proportion is found to be higher in ICU setting. However, presence of hyponatremia worsens the prognosis in ill patients. Objective: To find the prevalence and outcome of patients having hyponatremia on morbidity and mortality in PICU. Material and Methods: This prospective cohort study conducted at Pediatric Intensive Care Unit (PICU) in a tertiary care teaching hospital in Kerala during 6-month period. Results: Out of 410 patients, 253 had hyponatremia on admission with prevalence of 61.71%, 161 had norm natremia and 3 had hypernatremia. Hyponatremia was frequent among patients with pediatric risk of mortality score > 5 %. Severe hyponatremia was also associated with increase in length of PICU stay [p=0.024], increase in requirement of mechanical ventilation and mortality [p = <0.001] in comparison to milder group. Hence hyponatremia severity was independent risk factor of mortality in PICU, but might also confound other risk factors that render the children requiring prolonged hospital stay, mechanical ventilation and mortality. Conclusion: Hyponatremia is an independent prognostic factor for mortality: however, the reason for this remains unclear. Hence early recognition of hyponatremia and appropriate intervention will improve the outcome.